2018
DOI: 10.1007/s00256-018-2972-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of repeat CT-guided biopsy for suspected infectious spondylodiscitis

Abstract: Overall microbiologic yield of repeat CT-guided biopsy for patients with suspected infectious spondylodiscitis was low at 14.3%; however, a higher yield was identified in patients who were younger in age and not exposed to pre-biopsy antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In addition, although 95% of patients with positive blood culture had S. aureus bacteraemia, none of the patients had a CT guided biopsy. Previous studies suggest that initial biopsy is only positive in minority of the cases and has an even lower yield in patients with prior antibiotic exposure [24]. Contrary, a few other studies shown that the majority of bone biopsies yield S. aureus [22,13].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, although 95% of patients with positive blood culture had S. aureus bacteraemia, none of the patients had a CT guided biopsy. Previous studies suggest that initial biopsy is only positive in minority of the cases and has an even lower yield in patients with prior antibiotic exposure [24]. Contrary, a few other studies shown that the majority of bone biopsies yield S. aureus [22,13].…”
Section: Discussionmentioning
confidence: 95%
“…5,6 In patients with negative blood-cultures, CT-guided biopsy might be able to isolate causative agents of spondylodiscitis. 7 The rate of positive microbiological and/or histopathological findings varies considerably in the literature. Definitive factors that might influence or predict a positive microbiological or histopathological finding are not consistently reported.…”
Section: Introductionmentioning
confidence: 99%
“…Definitive factors that might influence or predict a positive microbiological or histopathological finding are not consistently reported. 7,8 The goal of our retrospective study was to evaluate a series of CT-guided biopsies in suspected spondylodiscitis in order to document rates of positive microbiological or histopathological findings in correlation to the site of CT-guided biopsy ( i.e . intervertebral disc or paravertebral soft tissue) and to identify possible factors that might predict a positive microbiological result.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional bone cultures theoretically could be affected by systemic antibiotic treatment before cultures are obtained and there is a concern that this could reduce culture yield. The common perception to hold antibiotics prior to bone biopsy; however, does not have convincing evidence (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Pathogen directed therapy has been reported to have a higher rate of success, so regardless, cultures are needed to plan therapy.…”
Section: Discussionmentioning
confidence: 99%